Effects of hyperpolypharmacy and potentially inappropriate medications (PIMs) on functional decline in older patients discharged from acute care hospitals. (July 2018) - Fabbietti, Paolo; Ruggiero, Carmelinda; Sganga, Federica; Fusco, Sergio; Mammarella, Federica; Barbini, Norma; Cassetta, Laura; Onder, Graziano; Corsonello, Andrea; Lattanzio, Fabrizia; Di Rosa, Mirko
Highlights: Hyperpolypharmacy and potentially inappropriate medications (PIMs) are frequent among older patients discharged from hospital. Hyperpolypharmacy and Beers violations might predict functional decline in older patients discharged from hospital. Hyperpolypharmacy might be associated with functional decline independent of PIMs. Abstract: Aim: To comparatively investigate the effects of hyperpolypharmacy and potentially inappropriate medications (PIMs) on functional decline in older patients after hospital discharge. Methods: Our series consisted of 733 patients aged ≥65 consecutively enrolled in a multicenter observational longitudinal study. PIMs were defined on the basis of updated versions of Beers and STOPP criteria. The occurrence of functional decline was defined as the loss of independency in at least 1 basic activity of daily living (BADL) from discharge through 3-month follow-up visit. Results: After adjusting for several potential confounders, hyperpolypharmacy (OR = 2.20; 95%CI = 1.11–4.37) and Beers violations (OR = 1.99; 95%CI = 1.17–3.49) were significantly associated with functional decline, while STOPP (OR = 1.10; 95%CI = 0.64–1.88) and combined Beers + STOPP violations (OR = 1.72; 95%CI = 0.97–3.05) were not. In logistic regression models simultaneously including both hyperpolypharmacy and PIMs, hyperpolypharmacy was always associated with functional decline (OR = 1.98; 95%CI = 1.0–3.97 in the model including Beers violations; OR = 2.19; 95%CI = 1.11–4.35 in the model including STOPP violations; OR = 2.04; 95%CI = 1.02–4.06 in the model including combined Beers and STOPP violations). Beers violations (OR = 1.89; 95%CI = 1.09–3.28) also remained significantly associated with the outcome in this latter analysis, but not STOPP or combined Beers and STOPP violations. Conclusions: Hyperpolypharmacy, and to a lesser extent Beers violations predict functional decline in older patients discharged from acute care hospitals, whilst STOPP criteria are no longer associated with the outcome after adjusting for potential confounders. Hyperpolypharmacy is associated with functional decline independent of PIMs.